MENINGKATKAN KREATIVITAS BERPIKIR TINGKAT TINGGI SISWA SD MELALUI MEDIA AUDIO VISUAL BERBASIS STEAM PADA SISWA SD - Siti Anisa Fatonah; Khavisa Pranata (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article discusses the improvement of elementary school students’ creativity of high- level thinking through STEAM-based Audio-Visual media. The research was conducted through observation, interview, and documentation. The subjects in the research involved 24 third-grade students of SDS Sa'adatuddarain, which consist of 13 male and 11 female students. The research sample was 24 students selected through a saturated sampling technique. The results indicate that there is an improvement in higher-order thinking skills through STEAM-based audio-visual media for the third- grade students of SDS Sa'adatuddarain. It can be seen from the students who obtained reading mastery average score of 80 in the good category in cycle 1 and cycle 2. Therefore, it is recommended for teachers and students of SDS Sa'adatuddarain to use this STEAM-based audio-visual learning media.